Achievement Testing Competence of Secondary School Teachers in Osun State, Nigeria - Olawale Ayoola Ogunsanmi; Victor Abiodun Lijofi; Abiodun Enitan Gbolagun (PAEDAGOGIA, 2025)
Tests properly designed in the classroom can provide teachers with accurate and useful information about their students. The study determined the content validity of an achievement test used by teachers and examined the test construction skills of the teachers in Osun State secondary schools. A descriptive research design was adopted for the study. The population consisted of public secondary school teachers in Osun state. A sample of 120 teachers was selected purposively from six Local Government Areas based on five core subjects offered in each school and 12 schools were selected using a simple random sampling procedure. Two research instruments: The test Construction Skills Inventory (TCSI) and Observation Records Sheet (ORS) were used for data collection. The TCSI possessed reliability estimates of 0.85. Data were analysed using frequency count and content validity index (CVI). The results showed that the achievement tests used by teachers in high schools are (CVI = 6.2, mean topic covered = 3.7, 59.7%) while middle schools are (CVI = 6.0, mean topic covered =3.4, 58%). This implied that both achievement tests used by secondary school teachers have moderate content validity. The results also revealed that the level of test construction skills is high (66, 55.0%), and a mean competence value of 3.2 for both middle and high school teachers is suitable enough to ensure proper achievement testing competence. The study concluded that the test construction skills of Osun State secondary school teachers are high enough to ensure adequate achievement testing competence